Biogas production from distillery slops using a multi-stage filter reactor - Demafelis, Rex B. (1990)
The performance characteristics of a newly designed Multi Stage Filter Reactor was investigated on the bases of gas productivity, COD removal, methane content and process stability. Distillery slops, a high strength industrial waste was used as a substrate in the anaerobic digestion. An average gas productivity of 25 liter gas per liter feed at slops COD content of 73,920 mg/liter. Average methane content and COD removal were 68.8% and 75.97%, respectively.